Study the release of nitrogen from coated urea granule: Modelling and experimental validation - THANH, TRINH HOAI (2016)
Urea. when applied to crops is vulnerable to losses from volatilization and leaching. Controlled-release fertilizer (CRF) enhances nitrogen use efficiency by plants which not only increases the crop yields but also contributes towards environmental pollution control in terms of the alleviation of hazardous gaseous emissions and water eutrophication.